Synthesis of Chiral 3‐Substituted 1, 3, 4, 5‐Tetrahydro‐1, 4‐benzo‐ diazepin‐2‐ones via a Domino Copper‐Catalyzed SN2/Coupling Reaction. Issue 16 (17th November 2015) - Lu, Dongming; Ma, Chang; Yuan, Shuai; Zhou, Lihong; Zeng, Qingle
Abstract: A novel protocol for the facile synthesis of chiral 3‐substituted 1, 3, 4, 5‐tetrahydrobenzo[ e ][1, 4]diazepin‐2‐ones via a domino reaction has been developed, which involves a cascade of SN 2 nucleophilic substitution and copper‐catalyzed CN coupling reactions of α‐amino acid amides and ortho ‐halobenzyl halides. This protocol has some merits, such as one‐pot process, easy operation, a wide scope of substrates. Furthermore, no heavy racemization occurs during the reaction. Abstract :